Foundations of Behavioral Health - Levin, Bruce Lubotsky; Hanson, Ardis (Springer, 2020)
Foundations of Behavioral Health is being completed in the midst of congressional debate over attempts to repeal the Patient Protection and Affordable Care Act (ACA) which was originally signed into law by Former President Barack Obama on 23 March 2010. However, debate over health-care reform is hardly new, with many attempts at health-care reform attempted during the previous (approximately) half century. Nevertheless, there are three basic reasons this textbook has been developed. First, health care is one of the most basic and important issues in the United States; however, health care is still not a right. Second, there continues to be expanded discontent, as well as frustration, with health-care delivery systems in the United States, particularly with access to services, treatment costs, and service outcomes. Third, behavioral health (i.e., alcohol, drug abuse, and mental health) delivery systems are disjointed from other behavioral health delivery systems and isolated from health-care delivery systems. Foundations of Behavioral Health examines the organization, financing, delivery, and outcomes of behavioral health services from both the United States and global perspectives. Our textbook covers many fundamental issues in behavioral health, including epidemiology, insurance and financing, health inequities, implementation sciences, lifespan issues, cultural competence, and policy, which also have implications for public health services and integrated health-care services. It also addresses topics of concern to health administrators, planners, policymakers, evaluators, and treatment professionals, including at-risk indigenous populations, individuals in the juvenile justice systems, individuals with intellectual and developmental disabilities, and individuals living in rural and frontier areas. The development and organization of Foundations of Behavioral Health